The order of thought and the order of words - Petronienė, Eglė (Kalbotyra, 2007)
From the point of view of translation strategy, translators seem to fall between two positions. Some of them (like Shapiro and his adherents) believe that the source text should sound completely neutral and natural in the target language. Typically, they prefer standard target language sentence patterns to achieve a smooth and transparent translation. Other translators (like Venuti and his followers) say that awkward wording in the target language should remain to remind the readers that they are reading a translation. The present article addresses this controversy with respect to one formal phenomenon – sentence patterns, or word order, – and one discourse phenomenon – the communicative status of entities described by sentences